Development And Validation Of A Sensitive Rp-Hplc-Pda Method For Assay Of Irbesartan In Pure And Pharmaceutical Dosage Forms - R. PRASHANTHI,; K. RAGHAVI,; M. SINDHURA,; B. ANUPAMA,; BUCHI N. NALLURI, (International Journal of Pharma and Bio Sciences, 2012)
A novel reverse phase-high performance liquid chromatographic (HPLC- PDA) method was developed for the analysis of Irbesartan (IRB) in pure and pharmaceutical dosage forms with LC conditions suitable for LC-MS detection. The chromatographic conditions comprised a reversed-phase C18 column (150 x 4.6 mm, 5 μ) with a mobile phase consisting of a mixture of methanol and formic acid (0.02% v/v in water) in the ratio 70:30 at a flow rate of 1 mL/min. Detection was carried out at 234 nm. The retention time of IRB was 5.24 min. The linear regression analysis data for the calibration plots showed good linear relationship in the concentration range 10-50μg/mL with a regression coefficient of 0.998. Limit of detection (LOD) was found to be 0.07 μg/mL and the method was found to be more sensitive than the published papers. The method was validated for assay, precision, recovery, ruggedness and robustness. The percent recovery and assay values were in the ranges of 99.23-102.87 and 99.82-101.16. The results of all the validation parameters were well within their acceptance values.